Parallel import of dispensed medicines: an analysis of the laws and practice in Malaysia / Zuraini Mohamad Redhuan, Hairanie sa'ban and Jacklyn Kiyun. - Mohamad Redhuan, Zuraini; sa'ban, Hairanie; Kiyun, Jacklyn (Faculty of Law, 2011)
Through the rapid growth of technology, communication and transportation that shade the countries geographical boundary, parallel import has becoming an important issue for international trade and management. Parallel import is the import and resale in a country, without the consent of the patent holder, of a patented product that has been legitimately put on the market oi the exporting country under a parallel patent. This stud} examines the law governing the practice of parallel import and observes the fundamental factors that persuade consumers' attitude towards parallel import in Malaysia and other countries. Some laws and regulations that are discussed in regards of parallel import are Trip Agreements, Doha Declaration, Patent Act and Free Trade Agreement. This study is aims to analyse the provisions on parallel import where the issue of non-counterfeit product imported from another country without the permission of the intellectual property owner will be analyse. The law will not only protect the right of original manufacturer, it will also prevent customer from consume hesitant prescribed dispensed medicine. The study adopts a qualitative method where the Poison Act 1952, Customs Act 1967, Patents Act 1983, Sale of Drugs Act 1952, Trade Mark Act 1976, Control of Drugs and Cosmetics Regulations 1984, Custom (Prohibition of Imports) Order 1998. Customs Duties Order 1996 and Customs Regulations 1977 are analysed and interviews are conducted with the Custom officers and officers from Pharmacy Department (National Pharmaceutical Control Bureau and Pharmacy Enforcement Unit). The research reveals that, there are loopholes in the laws and policies as there is no specific provision for parallel import to control the parallel importation of dispensed medicine in Malaysia. The research suggests ways to improve the laws on parallel import of dispensed medicine in Malaysia.